A study of academic resilience amongst first generation university students in South Africa - Meinert, Leigh (School of Education, 2015)
This study adopts a sociological approach to the issue of academic resilience amongst first generation university students in a developing world context. As suggested in the opening quotation above, this study aims to generate insight in to the structural conditions of first generation students who have accessed higher education and to better define the â€œoverwhelming oddsâ€ that are frequently deemed to be against them. More importantly perhaps, this study seeks to generate understanding about the manner in which these agents engage with their structural conditions and, in so doing, succeed in overcoming the effects of their natal conditions, or not. Margaret Archerâ€™s (2003) theory of â€œmodes of reflexivityâ€ , the nexus between structure and agency, is utilised as the conceptual framework for this study. This research project is therefore guided by the following 2 primary questions that, together with their related sub-questions, are motivated in more detail in Chapter 2 (refer to Section 2.8). All research questions will be featured in italics throughout this report. 1. How do first generation university students in a developing world context engage with their socio-cultural conditions? 1b) What are the distinctive aspects of the socio-cultural conditions of students in a developing world context? 2. Are some modes of reflexivity more conducive to academic resilience in undergraduate studies than others? 2b) What kinds of interventions can be put in place to serve first generation university entrants better?